The impact of imposing the new VAT & SD Act 2012: a study on the challenges Chevron faced due to the change of VAT Law - Shahriar, Md. Ahad (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.